PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAPRETURN SAHAM(Studi Kasus Pada â€œPerusahaan Manufaktur Sub Sektor Makanan Dan Minuman Periode 2010-2016â€) - Dewa Ayu Suci; Iwin Arnova (Universitas Prof.Hazairin,SH Bengkulu, 2019)
This research is intended to study the Effect of Operating Flow and Accounting Profits on the return of shares of the Food and Beverage Manufacturing Sub-Sector in the Indonesia Stock Exchange. The population in this study were 16 food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2010-2016. While this research sample was determined by purposive sampling method so that 9 samples were obtained during the study year. The method of analysis uses descriptive statistical methods with analysis of multiple regression analysis and hypothesis testing is done by t test. The calculation results obtained by linear regression equation, namely Y = 0.194 + 0.81X1 + 0.001 X1, with the value of the correlation coefficient (r) of 0.407 and the value of the detemination coefficient of 0.166. This shows that 16.6% of the dependent variable can be accessed by independent variables, while the remaining 83.4% is approved by other factors not included in the regression model. Partial test results (t test) show only the operating cash flow variable (AKO) associated with stock returns because the value of shares is 3,201 with ttable 2,000 so Ha is accepted and H0 is rejected, accounting variable variable (LA) is not in accordance with stock returns because it has value thitung is 1,415 with a table of 2,000, Ha is rejected and Ha is accepted.